Comparison of virtualization performance of Proxmox, OpenVZ, OpenNebula, Vmware ESX and Xen Server - Rycaj, Grzegorz (Journal of Computer Sciences Institute, 2019)
The aim of the article is to compare the performance of five popular virtualization solutions used in the private cloud model. The analysis was conducted for five virtualizers: Proxmox, OpenVZ, OpenNebula, Vmware ESX, Xen Server. OpenSSL, GeekBench and Phoronixtest-suite tools were used to perform performance tests. The comparison included selected encryption methods, data block size, and compilation speed